PENGARUH TINGKAT KESULITAN KEUANGAN DAN TINGKAT HUTANG TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR DI BEI - PRAMUDITA, NATHANIA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Conservatism is a principle which affects valuation in accounting, because it is conservative to this day still has an important role in accounting practices. Principles such as conservatism into consideration in accounting for financial statements for the company’s activities completed by the uncertainty. Conservatism is an accounting principle that if implemented will result in these figures tend to be high cost and debt. As a result, reported earnings tend to be too low. Such a tendency due to slow recognition of the principle of conservatism and accelerate revenue recognition of the cost.The purpose of this research was to test empirically the influence of the financial distress that proxy with z score and the level of debt that proxy with DER of accounting conservatism on the manufacturing companies listed on the Indonesian Stock Exchange (BEI) in the period 2006-2010. Testing the research was conducted using Multiple Linear Regression method. The result showed that (1) The financial distress have a positive effect of accounting conservatism, due to face an uncertain environment it takes a cautious attitude then with increasing levels of financial distress the company will be more conservative, (2) The debt has no effect of accounting conservatism. This is probably caused because the company has been careful in acting so it does not matter with a high or low levels of debt the company continues to use the principle of conservatism.